ANALISIS PENYAJIAN KARAKTER DAN ALUR CERITA PADA KOMIK VULCAMAN-Z - Musnur, Irfandi; Faiz, Muhamad (Narada : Jurnal Desain dan Seni, 2019)
Analysis of Character Presentation and Storyline in the Comic "Vulcaman-Z" aims to find out and identify visually how the presentation of characters and storylines in the comic Vulcaman-Z by Galang Tirtakusuma. This comic is a 4 point comic (yonkoma) or four panels, a slapstick action-comedy genre that is rarely found in the Indonesian comics industry. This comic also has several unique features such as the use of layouts, characters, colors, expressions, action lines, and word balloons. This research uses a descriptive qualitative method with interviews, literature study and observation data collection methods. The purpose of this research is the initial research conducted jointly with students to uncover several Indonesian comic artists’ styles which later become a study of revealing comic styles from Indonesia. As we know that Indonesian comics are still very influential with foreign comics, both Japanese and American. The comic style possessed by Indonesia does not yet have own characteristics, although some comic artists have tried to express the identity of Indonesia through cultural ornaments and stories. But the presentation and style of comics are still using or the same as the style that is outside. Based on this, this research is present as an effort to discover the characteristics of Indonesia in Comics or to give an idea to Indonesian comic artists to present new style contributions to Comics.